Developing English speaking skills: Getting used to speaking English in the family environment - Jingga Lydia Maharani; Sri Wahyuningsih (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
This study aims to report on the role of the family in helping students develop English speaking skills. A qualitative method was used, with data collected through questionnaires distributed to five EFL university students. The data obtained was analyzed using qualitative descriptive analysis techniques, where the results of questionnaires and interviews were categorized, compared and interpreted to describe the patterns that emerged. The findings show that becoming accustomed to speaking English in everyday life greatly aids in improving English speaking skills. The supportive role of the family plays a crucial part in helping students develop their cognitive abilities. Proper treatment and motivation at home are essential for this process. Additionally, the good habits and traits fostered within the family environment serve as guidelines for building a promising future. A positive family environment has a significant impact on enhancing speaking skills and makes learning English easier for a child. By incorporating vocabulary into daily activities, students are able to memorize and understand it more easily, as learning becomes enjoyable and habitual, leading to a more effective language acquisition process.